Fabrication and evaluation of a protruding Si-based printhead for electrohydrodynamic jet printing. (30th October 2017) - Pan, Yanqiao; Chen, Xinyuan; Zeng, Liangcai; Huang, YongAn; Yin, Zhouping
Abstract: A printhead that is compatible with Si-based processes and able to generate homogeneous micro- and nano-scale droplets plays an important role in electrohydrodynamic jet printing (E-jet printing) for the large-scale manufacturing. This paper proposes the design, fabrication and evaluation of a novel protruding Si-based printhead for E-jet printing. The protruding nozzle can concentrate the electrical field and restrain the lateral wetting so as to improve the jetting stability. However, it is a challenge to have both the protruding structure and a stable solution/voltage supply. Accordingly, a set of micro-manufacturing processes, as well as methods of adopting hydrophobic and insulation treatments, are also presented to stabilize the solution/voltage supply. The diameter and height of the protruding nozzle are 50 µ m and 60 µ m, respectively. Printing tests are performed using both quantum dots solution (CdSe/CdS/ZnS) and a mixed solution of glycerol, ethylene glycol and water. Feasibility of the protruding nozzle is proved by experiments that a stable meniscus with Taylor cone could form on the nozzle orifice, and fine dots (⩽30 µ m) could be printed successfully and continuously. The protruding design and micro-fabrication processes of the protruding Si-based printhead pave the way for the multi-nozzle E-jet printing with high efficiency and resolution.